El despido injustificado como forma de terminar la relación laboral frente a la falta de norma jurídica que lo regula en el Ecuador. - Roblez Ocampo, Jessica Estefanía (2023)
In this research project, specific measures will be analyzed in the workplace and from a point of view of collective bargaining, in view of how they have been occurring, that workers have been harmed. because behind their backs, measures and regulations have been issued for the benefit of the business sector Since ancient times, job separation has marked various aspects of economic origin, due to the fact that the employment areas are decreasing or, in turn, do not meet the necessary conditions and standards to provide the worker with a stable position in order to end those relationships. labor against the provisions of the legal norm. Being fired arbitrarily, exceeding the workers in their working hours, changing occupation, or being altered affects the worker and his entire family due to unemployment, causing great damages; The employer is obliged to pay those economic compensations, but we must take into account that these compensations provided for in the Labor Code are insufficient, seriously affecting those workers who maintain their homes, their family economy and that of the country, product of the dismissal that creates a legal vacuum. Since, if the compensations were reasonable and recognizing their labor force, it would be enough to survive until they find a new job, but due to the high rate of dismissals, this entails a series of inconveniences. In Ecuador, the great day-to-day problems that influence social development are evident, such as the untimely dismissal that seriously affects the worker, being the abuse by employers since there is no will of those workers in order to terminate the employment relationship. Thus, the need to regulate unjustified dismissal in our labor legislation is noted, so that the worker has a decent job and is not the product of violations, much less an 5 easy target for unemployment, so that the employer cannot disconnect him from his work area for no reason, and if in these cases his work is terminated, it must be based on what the law stipulates. Key Words: Workers' Rights, unfair dismissal, legal failures, dismissal, inequality.